An app-, web- and social support-based weight loss intervention for adults with obesity: the ‘HelpMeDoIt!’ feasibility randomised controlled trial - Sharon Anne Simpson; Lynsay Matthews; Juliana Pugmire; Alex McConnachie; Emma McIntosh; Elinor Coulman; Kathryn Hughes; Mark Kelson; Sarah Morgan-Trimmer; Simon Murphy; Olga Utkina-Macaskill; Laurence Anthony Russell Moore (Pilot and Feasibility Studies, 2020)
Abstract Background Social support has an important role in successful weight loss. The aim of this study was to assess the feasibility and acceptability of an app-, web- and social support-based intervention in supporting adults with obesity to achieve weight loss. Methods The intervention and evaluation methods were tested in a feasibility randomised controlled trial. Adults in the Greater Glasgow and Clyde Health Board area of Scotland with a body mass index ≥ 30 kg/m2 were recruited and randomised 2:1 (intervention to control). The feasibility and acceptability of the intervention and trial methods were assessed against pre-specified progression criteria, via process, economic and outcome evaluation. Three primary outcomes were explored: BMI, diet and physical activity, as well as a number of secondary outcomes. The intervention group had access to the HelpMeDoIt! intervention for 12 months. This encouraged them to (i) set goals, (ii) monitor progress and (iii) harness social support by inviting ‘helpers’ from their existing social network. The control group received a healthy lifestyle leaflet. Results One hundred and nine participants were recruited, with 84 participants (77%) followed-up at 12 months. The intervention and trial methods were feasible and acceptable. Participants and helpers were generally positive. Of the 54 (74%) participants who downloaded the app, 48 (89%) used it. Interview data indicated that HelpMeDoIt! promoted social support from existing social networks to support weight loss. This support was often given outside of the app. Outcomes were compared using linear regression models, with randomised group, the baseline measurement of the outcome, age and gender as predictor variables. These analyses were exploratory and underpowered to detect effects. However, all pre-specified primary outcome effects (BMI, diet and physical activity) had wide confidence intervals and were therefore consistent with clinically relevant benefits. Objective physical activity measures perhaps showed most potential (daily step count (p = 0.098; 1187 steps [− 180, 2555])) and sedentary time (p = 0.022; − 60.8 min [− 110.5, − 11.0]). However, these outcomes were poorly completed. Conclusions The study demonstrated that a novel social support intervention involving support from participants’ close social networks, delivered via app and website, has potential to promote weight loss and is feasible and acceptable. Trial registration ISRCTN, ISRCTN85615983 . Registered 25 September 2014